Indicator Based Vulnerability Assessment of Chhayanath-Rara Municipality, Western Nepal: DOI: 10.32526/ennrj.18.3.2020.21 - Bahadur Budha, Padam; Paudyal, Kabiraj; Ghimire, Motilal (Environment and Natural Resources Journal, 2020)
The dense settlements at the eastern hills of Rara Lake are at higher risk of existing landslides. Seepage of water from the lake has increased erosion rates, exaggerating the threats to villages. People are worried due to the potential of inadvertent disaster, therefore it became necessary to estimate the vulnerability of the communities and inform concerned authorities. Setting this requirement as an objective, underlying influencing indicators were assessed. The vulnerability assessment was based on the scoring of the responses emanated from indicator-based household's survey. These scores were summed up to generate indices and also mapped with their true locations. Vulnerability scores ranged from 16.50 to 21.75 and were categorized into five classes after standardization. A moderate vulnerability was exhibited by 33.08% of households sampled. High and very high categories of vulnerability occupied 18.80% and 4.51% of households, respectively. Field observation showed solitary households built away from village clusters were highly vulnerable. Most households showed moderate vulnerability and characteristics like stones/mud-built houses, firewood as a primary fuel, decreasing forests and grasslands, increasing temperatures, and decreasing rainfall were major influencing indicators for higher vulnerability in the research area.